2009
DOI: 10.1111/j.1467-839x.2009.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal perceptions and metaperceptions of relationship closeness, satisfaction and popularity: A relational and directional analysis

Abstract: Relationship closeness, satisfaction in interaction, and popularity in mainland China was investigated using a methodological relational approach, which stresses the bidirectional nature of perceptions and metaperceptions. Two studies were conducted: one involving 164 dyads and the other 20 five-member groups; participants were college students of both sexes who were well acquainted with one another. Major results are: (i) liking perceptions and metaperceptions are predominately relational in nature; (ii) assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(44 reference statements)
2
6
0
Order By: Relevance
“…Indeed, meta-analytic results indicate that the correlation between self-and supervisor performance ratings is very similar for samples from the U.S. and Asian cultures (Heidermeier & Moser, 2009). With regard to metaperceptions specifically, we are aware of one study examining metaperceptions in China (Ho & Chau, 2009). Results from that study were very similar to those from Western samples, again implying that the phenomena under investigation here are similar across cultures and that the current results would generalize.…”
Section: Limitationssupporting
confidence: 81%
“…Indeed, meta-analytic results indicate that the correlation between self-and supervisor performance ratings is very similar for samples from the U.S. and Asian cultures (Heidermeier & Moser, 2009). With regard to metaperceptions specifically, we are aware of one study examining metaperceptions in China (Ho & Chau, 2009). Results from that study were very similar to those from Western samples, again implying that the phenomena under investigation here are similar across cultures and that the current results would generalize.…”
Section: Limitationssupporting
confidence: 81%
“…Although we cannot definitively conclude to what degree these findings will generalize to a Western context, we would expect that the desire for, and process of, forming metaperceptions is largely universal. Consistent with this assertion is a recent study using Chinese samples that revealed similar metaperception patterns as those identified by Western researchers (Ho & Chau, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, recent research (Ho and Chau 2009) has pointed to the methodological problems inherent in studying people's social perceptions in interpersonal contexts, as the perceptions may also reflect projections of personality processes. Instead, we just note that there seems to be a systematic relationship between peer affiliation perceptions related to achievement goals and the adoption of such goals.…”
Section: Discussionmentioning
confidence: 98%